How blue light affect sleep - Julia Mikulska; Kamila Skoczylas; Sebastian Rokicki; Katarzyna Schok (Kazimierz Wielki University, 2023)
Many external factors affect human sleep. One of them is visible light. Its effect on the human body consists in synchronizing the biological clock in the suprachiasmatic nuclei of the hypothalamus with the 24-hour solar cycle. The short fraction of light waves perceived by humans as blue waves is the strongest factor that synchronizes the circadian system, which maintains the internal homeostasis of many biological and psychological rhythms. This impact depends on the amount, duration and time of exposure to blue light during the day. Exposure to blue light during the day is important for inhibiting the secretion of melatonin, a hormone produced by the pineal gland and playing a key role in entraining the circadian rhythm. While exposure to blue light is essential for maintaining the body's well-being, alertness, and cognitive abilities during the day, chronic exposure to low-intensity blue light right before bedtime can have serious consequences for sleep quality, circadian phase, and cycle duration. That is why the right amount and the right time of exposure to blue light are so important.